Consequencialismo judicial na suspensão de segurança nos julgamentos de direito regulatório - Kellner, Alexander Leonard Martins (2019)
The relationship between the interpretation of legal norms and the realization or concretization, based on consequences, of constitutionally assured purposes seems increasingly frequent in the jurisprudence of the Brazilian courts. This is because, judges, appeal court judges and ministers appear to introduce a logic and juridical rationality based on consequentialist arguments when rendering judicial decisions. It happens that, when the judicial authority bases a certain decision by analyzing the consequences produced by it and possible alternatives, the decision-maker tends to elaborate its reasoning based on scientific – and, therefore, extra-legal – criteria of adequacy. The problem is that – at least in principle – jurists do not have the epistemological ability to correctly handle those criteria. For this reason, this paper will analyze the jurisprudence of the Superior Court of Justice (STJ) in the rendering of decisions in the context of requests for suspension of security related to the Regulatory Law, with the aim to verify possible problems related to the positive dimension of consequentialist reasoning in such decisions. From this analysis, then, this study will get to the conclusion of suggesting to the STJ ministers, when judging requests for suspension of security under the Regulatory Law, that, based on a “second order justification” criteria – which is based on the principle of equality –, they use a “second order decision”, applying always 4 (four) of the 5 (five) steps of the analysis of regulatory impact, in order to better support the decision-making process.